Implementasi Business Process Modeling dalam Workflow Aplikasi Monitoring Electronic Data Capturer - Umi Proboyekti; Charoline Septa; Budi Susanto (Fakultas Teknologi Informasi, 2022)
Business Process Modeling (BPM) is a data-based visual representation to model business workflows to optimize business processes. BPM notations make the model easy to understand for all stakeholders who play a role in developing business processes. This paper will describe implementing BPM in the Electronic Data Capturer (EDC) Monitoring Application (EDCMA) workflow. The workflow modeling process uses Bonitasoft software that includes business process creation for user interface and process engine. EDCMA is a process to solve the problems in the EDC terminal repair process and the submission as a new merchant. Based on the existing manual procedure of EDCMA, the new EDCMA process model uses electronic form and semi-automatic processing that implement some Bonitasoft BPM features to develop a high-fidelity application prototype. In the evaluation process, we develop some scenarios with data tests that occur in manual procedures. Based on the evaluation, the prototype has successfully represented the entire process that occurs on each feature. In the future, developing EDCMA that uses web and mobile application frameworks will provide the EDCMA system for end-users.